2020
DOI: 10.1371/journal.pone.0232484
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ views and experiences of prescribing oral anticoagulants for stroke prevention in atrial fibrillation: A qualitative meta-synthesis

Abstract: Background Globally, over 33 million people have atrial fibrillation (AF). In eligible patients, oral anticoagulation (OAC) is recommended for stroke risk reduction. Despite recent increases in OAC prescribing, global under-prescription to high-risk AF patients and inappropriate prescription to low-risk patients is leading to unnecessary risk of stroke and haemorrhage. This metasynthesis explored clinicians' beliefs and experiences regarding OAC prescription to AF patients, highlighting barriers to stroke prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 29 publications
4
21
0
Order By: Relevance
“…This is potentialized by the possibility of being held accountable for harmful effects of the drug. 118 Some strategies must be considered to increase adequate OAC use in patients with AF, including educational interventions, providing adequate support for OAC management with warfarin and higher availability and access to NOAC. Future studies using both quantitative and qualitative methodologies are needed to further specify the reasons for the incorrect use of antiplatelets for stroke prevention, disclosing opportunities for effective interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This is potentialized by the possibility of being held accountable for harmful effects of the drug. 118 Some strategies must be considered to increase adequate OAC use in patients with AF, including educational interventions, providing adequate support for OAC management with warfarin and higher availability and access to NOAC. Future studies using both quantitative and qualitative methodologies are needed to further specify the reasons for the incorrect use of antiplatelets for stroke prevention, disclosing opportunities for effective interventions.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described in the literature, the underuse of OAC in individuals who would primarily benefit from this medication may occur for many reasons. 11,[28][29][30] Besides formal contraindications for the OAC therapy, it has been reported advanced age with higher risk of bleeding, more severe comorbidities with low predicted overall survival, low patient´s compliance, insufficient structure in the public health facilities to perform regular international normalized ratio monitoring, doctor´s concern about the low patient´s comprehension of AF and the risk of complications as bleeding as important barriers to the use of OAC , including for the secondary prevention of stroke. 11,[28][29][30] In the public health context, it is important to know the inter-regional differences to better understand the occurrence of chronic and disabling conditions.…”
Section: Af Related Stroke Outcomes and Anticoagulationmentioning
confidence: 99%
“…Consequently, prescribing decisions were seen to be influenced by prescriber preferences, which could be a barrier to DOAC use if warfarin was favoured. 41 Some suggested that longer consultations were needed but noted it would not be feasible due to a shortage of clinicians in the healthcare service. Required additional time was also noted to add extra spending in already perceived cost-conscious healthcare system.…”
Section: Discussionmentioning
confidence: 99%